MEMBANGUN EKONOMI ISLAM DENGAN MELESTARIKAN LINGKUNGAN - Saputro, Anip Dwi (IKONOMIKA, 2016)
Abstract-Islam in strengthening the social orientation among Muslims, then he introduced the concept of an obligation together, in which individual responsibility can be done by other individuals. This is called the fardhu kifayah. This concept emphasizes on meeting the needs of society and urge individuals to strive to fulfill it. With farming and organic farming catfish will create food and financial independence for Muslim families in order to achieve an economic independence Islam halalan thoyiban.By utilizing the land around our house for dimnfaatkan as land to grow crops or raise livestock organically catfish will be generated increase in financial income and food security are highly nutritious. It will be directly proportional to the increase in the welfare of Muslim families which have been considered weak, and be able to build an Islamic economic kemandiriian significantly in the society.Based on the survey we did in society in general, the needs of organic vegetables and organic catfish has been felt at the increasing demand of today's society. With the increasing prevalence of information is growing, people are now faced with the basic necessities of food is good and healthy for their families. People are starting to think and act real to abandon the use of chemicals that enter the intake of food that they consume every day.